Pengaruh Reward dan Komitmen Terhadap Kepuasan Kerja Karyawan pada Montana Syariah Hotel Banjarbaru - Kadir, Abdul; Anshori Muksin (Universitas Hang Tuah, 2022)
The purpose of this study was to determine and analyze the effect partially and simultaneously on reward and employee commitment variables on job satisfaction at Montana Syariah Hotel Banjarbaru. The type of research used in this research is correlational research with quantitative methods, namely research conducted by collecting data to find out whether there is a relationship between reward variables and employee commitment to job satisfaction at Montana Syariah Hotel Banjarbaru. The population of this study were all 47 employees of Montana Syariah Hotel Banjarbaru. In this study, researchers used a saturated sample, where all 47 employees were used as samples. Data collection techniques using questionnaires, documentation, interviews, and observation. Validity and reliability tests were carried out on research instruments. Data were analyzed with multiple linear regression analysis with the classical assumption test. The results of the study show that rewards and employee commitment simultaneously and partially have a significant effect on job satisfaction of the employees of Hotel Montana Syariah Banjarbaru. Rewards have a dominant influence on job satisfaction of Hotel Montana Syariah Banjarbaru employees.